2019
DOI: 10.3389/fmicb.2019.01688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Peptide, RP557, for the Broad-Spectrum Treatment of Wound Pathogens and Biofilm

Abstract: The relentless growth of multidrug resistance and generation of recalcitrant biofilm are major obstacles in treating wounds, particularly in austere military environments where broad-spectrum pathogen coverage is needed. Designed antimicrobial peptides (dAMPs) are constructed analogs of naturally occurring AMPs that provide the first line of defense in many organisms. RP557 is a dAMP resulting from iterative rational chemical structural analoging with endogenous AMPs, human cathelicidin LL-37 and Tachyplesin 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…In contrast, bactericidal antibiotics cause cell death (Schwalbe et al, 2007). Several studies have suggested that in general terms, bacteriostatic and bactericidal activities can be linked to MOA (Finberg et al, 2004;Woodburn et al, 2019;Yasir et al, 2019), though exceptions exist (Finberg et al, 2004). In the following, we present methods to determine the bactericidal activity of HDPs, as well as methods to look at membrane perturbation.…”
Section: Biological Assays To Determine Moamentioning
confidence: 99%
“…In contrast, bactericidal antibiotics cause cell death (Schwalbe et al, 2007). Several studies have suggested that in general terms, bacteriostatic and bactericidal activities can be linked to MOA (Finberg et al, 2004;Woodburn et al, 2019;Yasir et al, 2019), though exceptions exist (Finberg et al, 2004). In the following, we present methods to determine the bactericidal activity of HDPs, as well as methods to look at membrane perturbation.…”
Section: Biological Assays To Determine Moamentioning
confidence: 99%
“…Therefore, a monotherapy acne treatment that is highly potent with a reduced likelihood of developing antimicrobial resistance and with anti-inflammatory activity is urgently needed. Designed antimicrobial peptides (dAMPs) are laboratory synthesized peptides that are rationally designed analogs of naturally occurring AMPs, which provide the first line of defense against invading pathogens in all multicellular organisms [8][9][10]. dAMPs, also known as host defense peptides, have direct antibiotic activities in addition to modulating immune responses [8].…”
Section: Designed Antimicrobial Peptidesmentioning
confidence: 99%
“…Fungi and bacteria do not develop resistance against the dAMPs [16][17][18]. The rapid destruction of pathogenic cells by dAMPs infers a theoretical reduced likelihood of developing bacterial resistance.…”
Section: Discussionmentioning
confidence: 99%